Exploring solution spaces for nutrition-sensitive agriculture in Kenya and Vietnam - Timler, Carl; Alvarez, Stéphanie; DeClerck, Fabrice; Remans, Roseline; Raneri, Jessica; Estrada Carmona, Natalia; Mashingaidze, Nester; Chatterjee, Shantonu Abe; Chiang, Tsai Wei; Termote, Celine; Yang, Ray-Yu; Descheemaeker, Katrien; et al. (Elsevier, 2021)
Smallholder agriculture is an important source of livelihoods in South Asia and sub-Saharan Africa. In these regions the highest concentrations of nutritionally vulnerable populations are found. Agricultural development needs to be nutrition-sensitive, and contribute simultaneously to improving household nutrition, farm productivity and environmental performance. We explored the windows of opportunities for farm development and the potential of crop diversification options for meeting household dietary requirements, whilst concurrently improving household economic performance in contrasting smallholder farm systems in Kenya and Vietnam. Farm and household features and farmer perspectives and priorities were integrated into a farm-household model that allowed quantification of a diverse set of nutritional, labour and productive indicators. Using a multiobjective optimization algorithm, we generated ‘solution spaces’ comprising crop compositions and management configurations that would satisfy household dietary needs and allowed income gains. Results indicated sitespecific synergies between income and nutritional system yield for vitamin A. Diversification with novel vegetables could cover vitamin A requirements of 10 to 31 extra people per hectare and lead to greater income (25 to 185% increase) for some households, but reduced leisure time. Although the Vietnamese sites exhibited greater nutrient system yields than those in Kenya, the household diets in Kenya had greater nutrient adequacy due to the fact that the Vietnamese farmers sold greater proportions of their on-farm produced foods. We conclude that nutrition-sensitive, multi-method approaches have potential to identify solutions to simultaneously improve household income, nutrition and resource management in vulnerable smallholder farming systems.